Jesus As A Special Messiah - Pangeran Manurung (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
The problem in this essay lies in the issue of the Messiahship of Jesus which is thought to contain defects. Jesus is deemed unworthy of the title